Phylogenetic Relationships of Grasshoppers (Orthoptera) in Rice Field Ecosystems of Parigi Moutong Regency Based on Morphological Characters - Mia Pinasti Azizah; I Made Budiarsa; Manap Trianto; I Nengah Kundera; Abdul Ashari; Zulaikhah Dwi Jayanti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Grasshoppers are insects belonging to the order Orthoptera, which comprises a highly diverse group of species distributed across various ecosystems, including agricultural habitats such as rice fields. This study aimed to analyze the phylogenetic relationships among Orthopteran grasshoppers inhabiting rice field ecosystems in Parigi Moutong Regency based on morphological characters and to describe the clustering patterns of the species identified in the area. Sampling was conducted in rice fields using an exploratory survey method with free collection techniques. Species identification was carried out through the examination of morphological characteristics using biodiversity references and taxonomic identification keys. Phylogenetic relationships were analyzed using the Unweighted Pair-Group Method with Arithmetic Average (UPGMA) implemented in the PAleontological STatistics software (PAST 4.03), while Principal Component Analysis (PCA) was performed and visualized in a biplot to support the clustering results. A total of nine grasshopper species were identified: Phaneroptera falcata, Oxytauchira brachyptera, Scudderia texensis, Atractomorpha crenulata, Tettigonia viridissima, Conocephalus fuscus, Phlaeoba infumata, Oxya serville, and Phlaeoba fumosa. The phylogenetic analysis grouped the species into two major clusters with three levels of relationship. A very close relationship was observed between Phlaeoba infumata and Phlaeoba fumosa (similarity index [SI] = 91%). A close relationship was found between the subclusters consisting of Atractomorpha crenulata, Phlaeoba infumata, and Phlaeoba fumosa, and those consisting of Oxytauchira brachyptera and Oxya serville (SI = 62%). In contrast, a more distant relationship was observed between Conocephalus fuscus and the group comprising Scudderia texensis, Phaneroptera falcata, and Tettigonia viridissima (SI = 47%). These phylogenetic patterns were supported by the PCA biplot, in which P. fumosa, P. infumata, O. serville, and O. brachyptera were positioned within the same component, whereas S. texensis, P. falcata, and T. viridissima occupied different regions, and C. fuscus was clearly separated from the other species. This study provides scientific information on morphology-based phylogenetic relationships among grasshopper species in rice field ecosystems, which may serve as a foundation for taxonomic studies and as a reference for biology education concerning grasshopper phylogeny.